All power to Health. Trachoma and Argentinian migration policies in the first half of the twentieth century (Quinto Sol, 2016)
In this article, we studied the reception of immigrants with trachoma in the Port of Buenos Aires between 1908 and 1943, based on the relationshipbetween the speeches of doctors and the concrete practices of rejection. We analyze the theories of Argentine trachomatologists and elsewhere, and then compare them with the construction of categories of statistics of the Directorate General of Migration during the first half of the twentieth century and the performances of the different nationalities of the granular ones rejected. The study of the links between the discourses and practices reveals an over-representation and stigmatization of Syrian immigrants, while the construction of a myth about Jewish immigrants, Russians, Hungarians and Egyptians, among others. Such imagery is rooted in both nationalism and international exchange of trachomatologists on trachoma etiology, history and epidemiology and on legal and practical ways of selecting immigrants considered desirable.
Keywords: trachoma; immigration; health inspection; transnational public policies